Kajian Efektivitas Penataan Pedagang Kaki Lima pada Jalur Pedestrian Cicadas, Kota Bandung - Muhamad Rizal; Verry Damayanti (UNISBA Press, 2022)
Abstract. The problem of pedestrian facilities in urban areas in Indonesia is a pedestrian need that has not been met, both qualitatively and quantitatively. Pedestrian paths are built to limit human movement and avoid using lanes as a means of transportation. The informal sector activities that we often encounter in urban areas are street vendors, namely small-scale economic activities. To manage and develop the growing number of street vendors, the government issued Bandung City Regulation no. 04 of 2011 concerning the Composition and Guidelines of street vendors. The Bandung City Government revived 602 street vendors stalls on the Cicadas pedestrian area without any eviction efforts. Based on the description above, the authors are interested in raising the title, namely: